Challenges in emergency remote teaching among Malaysian public elementary school teachers - Lee, Yong Keow (International Association of Online Engineering, 2021)
The purpose of this study was to explore challenges public elementary school teachers faced when conducting emergency remote teaching duringpandemic in Malaysia. The scope of the study was limited to remote teachingwhich was conducted between Mar 2020 and December 2020, when Malaysiagovernment urged an emergency national lockdown to stop the spread of coronavirusin the country. This study adopted qualitative, case study research design.Ten public elementary school teachers were sampled using a purposive samplingmethod. Semi-structured interviews were employed to gain the insights of teachers’challenges in implementation of emergency remote teaching. The data wereanalysed using thematic analysis and a facilitation of Nvivo 12 programme.There were six main themes emerged on teachers’ challenges, which were (1)Directing gateway; (2) Lack of skill and knowledge; (3) Unable to meet all needs;(4) Unable to engage students; (5) Lack of support from parents; and (6) Had noproper guideline. As teachers were the key persons in determining the functionality,effectiveness and development of future remote teaching, hence it was extremelycrucial to listen to teachers’ voices and figure out how these educatorscould be supported in the future to benefit the learners and communities.